Job descriptions as drivers for changes in practice patterns: a cross-sectional survey of Nurse Practitioners in Norway - Else Turid Pedersen; Mette Tøien; Lisbeth Fagerström; Linn Hege Førsund (BMC Nursing)
Abstract Background Nurse Practitioners (NPs) are pivotal in transforming healthcare by bridging gaps in delivery and improving patient outcomes through advanced clinical expertise. Internationally, NPs often have clear job descriptions and significant autonomy. However, in Norway, the lack of standardized role definitions creates challenges. This study explores the integration of NPs into the Norwegian healthcare system, highlighting variations in practice patterns due to limited regulatory clarity and standardized job descriptions. Establishing national regulatory mechanisms is essential for the consistent development and integration of NPs, ultimately enhancing healthcare service quality. Aim This study aims to explore the demographic and professional characteristics of NPs in Norway and analyse the influencing factors on changes in their practice patterns following the completion of NP education. Methods This study utilized a quantitative, cross-sectional design to collect data over a four-month period, from mid-October 2023 to mid-February 2024. Data analysis was performed using Stata® 18.0, focusing on demographic, education, work condition, and changes in practice patterns following NP education, and specialist approval. Categorical variables were presented as frequencies with proportions, while continuous variables were presented as means with range. Logistic regression was used to examine associations between changes in practice patterns and factors such as workplace, graduation time, and job description, employing both univariable and multivariable analyses. Results The sample included 95 participants, the majority of whom were educated in the South-Eastern Norway, and 74% had obtained specialist approval. The results show that 66% of participants reported changes in practice patterns after completing NP education, but only 26% had formal job descriptions. Statistical analysis revealed a strong association between having job descriptions and changes in practice patterns (OR 9.5, p = 0.005). Those who graduated after 2020 were less likely to report changes compared to those who had graduated earlier (OR 0.18, p = 0.016). Conclusion Job descriptions are critical drivers for changes in practice patterns among NPs, but few participants reported having such descriptions. This underscores the need for the healthcare system to assess and tailor NP job descriptions to meet its needs and maximize competency utilization.